Hyperosmolar Coma: Diagnostic Difficulties on the Clinical Example - L. M. Farkhutdinova (Архивъ внутренней медицины, 2025)
Hyperosmolar hyperglycemic state is an acute complication of diabetes mellitus, the mortality rate of which reaches 50 %. One of the reasons for the unfavorable outcome is untimely diagnosis, which is often due to insufficient awareness of doctors regarding the features of clinical and laboratory manifestations of this diabetic complication. Hyperosmolar state often develops in older patients with polymorbidity, and neurological symptoms predominate in the clinical picture, which also complicates diagnosis and causes diagnostic errors. The article presents a clinical case of hyperosmolar hyperglycemic state, the diagnosis of which caused difficulties at all stages, including postmortem pathological examination. Initially, acute cerebrovascular accident was assumed, then the patient’s severe condition was associated with acute myocardial infarction, and based on the results of the pathological examination, a conclusion was made about sepsis and septic shock. Review of the patient’s medical history showed that the most probable diagnosis was hyperosmolar state, which developed as a result of decompensation of diabetes mellitus against the background of the inflammatory process. Severe dehydration of the patient, as the cause of her soporous state, was confirmed by the data of examination and laboratory and instrumental examination: dry skin and mucous membranes, small amount of urine, signs of blood thickening and prerenal acute renal failure. At the same time, the absence of obvious focal neurological disorders, clinically significant changes in the cardiovascular system, fever and hemodynamic disturbances did not allow, in our opinion, to associate the patient’s severe condition with acute cerebrovascular accident, myocardial infarction or septic shock. Dehydration was complicated by the development of disseminated vascular coagulation syndrome, gastrointestinal bleeding and hemorrhagic shock with a fatal outcome. This clinical case demonstrates that in differential diagnostics of diseases a more reliable approach is the analysis of the clinical picture from the point of view of the pathogenesis of disorders. Analysis of such clinical situations can serve as an aid for doctors in diagnosing hyperosmolar state.